ISSUES OF IMPROVING THE CULTURE OF EFFECTIVE USE OF THE INTERNET AND SOCIAL NETWORKS - Khabiba Naimovna Oblomuradova (PT. Antis International Publisher, 2025)
Objective: This study examines strategies for enhancing the culture of effective Internet and social media usage, particularly in mitigating the negative impacts of online information on young people's consciousness and lifestyles. Method: A qualitative approach is employed, utilizing document analysis and case studies to assess digital literacy programs, regulatory measures, and behavioral patterns associated with social media engagement. Results: Findings indicate that while internet accessibility has significantly improved, the lack of digital awareness exposes users, especially youth, to misinformation, cyber threats, and manipulative content. Effective interventions, including media literacy education, legal frameworks, and ethical guidelines, are crucial in fostering responsible digital engagement. Novelty: This study provides a comprehensive analysis of the socio-cultural and legal dimensions of internet usage, emphasizing the role of digital literacy in countering information attacks. By integrating policy recommendations and educational strategies, the research contributes to the broader discourse on digital ethics and media responsibility in the digital era.